OSCH-LEACH: Optimum Secondary Cluster Head Selection for LEACH Protoco (Al-Mansour Journal, 2022)
A wireless sensor network consists of a bundle of sensor nodes which is using for monitoring and recording variety phenomenon’s such as pressure, wind direction and speed, home security, machine failure diagnosis and biological detection. When the information collected and be together in an energy efficient manner help the sensor network to operate for long interval. The transmitted data between sensor nodes and Base station is as a result of fusion data in (WSN). And the LEACH (Low Energy Adaptive Clustering Hierarchy) protocol come with solutions for all data collection problems, when the clusters are arranged in self- organized manner, but it still suffering from some downside that can cause fatal problems. To save the energy and based on the research of LEACH protocol, an optimum secondary cluster head low energy clustering protocol OSCH-LEACH is proposed in this paper. In the new protocol, in any round when the cluster head located in not good place -near the edge of the cluster and far away from many sensors - Cuckoo search algorithm is suggested to find the optimum secondary cluster head that take the role of the primary cluster head for those remote sensors i.e. aggregate data from those remote sensors and send the report to the primary cluster head. The experimental results show that OSCH-LEACH performs better than LEACH protocol. It not only extends the lifetime of the network, but also improves the energy efficiency by increasing the settle down and unsettle down period, number of alive nodes with time, and minimize energy consumption.
Keywords: LEACH protocol, clustering of WSN; optimization algorithms; power consumption of WSN